Carbon footprint of biofuels production from forest biomass using hot water extraction and biochemical conversion in the Northeast United States. (15th February 2022) - Therasme, Obste; Volk, Timothy A.; Fortier, Marie-Odile; Kim, Youngwoon; Wood, Christopher D.; Ha, HakSoo; Ali, Atif; Brown, Tristan; Malmsheimer, Robert
Abstract: This study assessed the cradle-to-grave life cycle greenhouse gas (GHG) emissions of ethanol production via the fermentation of sugars derived from hot water extraction (HWE) of forest biomass under two processing energy scenarios (biomass, natural gas). The energy source was a key driver of the climate change benefits of ethanol production. Compared to petroleum gasoline, the lifecycle GHG emissions of ethanol fuel were 78% lower for the biomass scenario while the natural gas scenario resulted in 2% increase of GHG. Monte Carlo analysis revealed that when the input variable parameters were allowed to vary by 20% from their baseline value, the biomass scenario was always compliant with the 60% GHG reduction requirement for cellulosic ethanol. Measures to improve the energy efficiency of the biorefinery per unit of ethanol produced ( i.e. increase ethanol yield or reduction in energy consumption) could result in ethanol fuels produced under the natural gas scenario with GHG emissions equal to or less than those of petroleum gasoline. The potential for ethanol from forest biomass in the Northeast United States to contribute to the decarbonization process is heavily dependent on the process energy resources chosen to power the biorefinery and the characteristics of the designed conversion process. Graphical abstract: Image 1 Highlights: Carbon footprint of ethanol from forest biomass hot water extract was assessed. A natural gas and a biomass scenario for process energy were defined. Biomass scenario resulted in low carbon biofuels with 78% less GHG than gasoline. Natural gas scenario emitted 2% more GHG emissions than gasoline. The most influential parameters included ethanol yield and energy needed for HWE.